Leveraging Corporate Social Responsibility (CSR) to Address Eco-Anxiety - Marczinka, László (2024)
The purpose of this study is to explore the potential intersection of Corporate Social Responsibility (CSR) and eco-anxiety and how the CSR as a concept can be leveraged if ecopsychological dimensions are considered and incorporated into its framework. During the research, an exploratory and a casual question are guiding the research process which are: RQ1: What could be the strategies and practices employed by companies to address eco-anxiety for internal stakeholders? RQ2: To what extent are Corporate Social Responsibility (CSR) initiatives of Patagonia trying to address eco-anxiety. The literature review offers a comprehensive analysis of existing literature, introducing various perspectives and definitions related to eco-anxiety and CSR. This thesis employs a theory-driven content analysis approach to investigate the relationship between eco-anxiety and CSR practices. Furthermore, it provides an analysis on how CSR initiatives by Patagonia are aligning with addressing eco-anxiety among different stakeholders. In addition, the research provides a list of practices to alleviate eco-anxiety introduced in an individual approach which consist of 16 initiatives classified into 4 groups, namely “Physical and emotional”, “Proactive, sustainable”, “Educational and professional” and “Community based” practices. During the research, this list is translated into an organizational approach, entailing 16 initiatives and 4 new groups namely: “well-being and supportive”, “policies and organizational”, “awareness and educational”, “community engagement and collaborative” practices in the context of internal stakeholders to establish a guideline for different business entities. By examining individual and organizational practices to mitigate eco-anxiety and linking them to CSR strategies, the study contributes to advancing theoretical understanding in the fields of ecopsychology, CSR, and employee well-being. The conclusion sections aim to answer the research questions and draw key findings. The findings highlight the strengths and challenges of current CSR initiatives, eco-anxiety and dovetailing the two terms, emphasizing the need for integrated approaches that prioritize stakeholder well-being alongside environmental sustainability. The recommendations for future research and the limitations of the study are mentioned.